Pengaruh Perilaku Phubbing Terhadap Intensitas Komunikasi Pada Pengunjung di Area Publik M Bloc Space - Fatimah Salsabilla; Budiaman Budiaman; Achmad Nur Hidayaht (WISSEN : Jurnal Ilmu Sosial dan Humaniora, 2024)
The study aims to find out the influence of phubbing behavior with communication intensity on visitors in the public area of M Bloc Space. The design of the study uses quantitative research with sampling techniques used with accidental samplings. The sample in this study is a visitor to the public area of M Bloc Space as an active smartphone user with a total of 70 respondents. The data collection method used is a scale of phubbing behavior and communication intensity. The results of this study show that Phubbing behavior has a positive and significant influence on Communication Intensity because the t count value is greater than the t table and the significant value is less than 0.05 so the Ha hypothesis is accepted.